Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1680/stbu.12.00068
|View full text |Cite
|
Sign up to set email alerts
|

Shear behaviour of steel-fibre-reinforced concrete simply supported beams

Abstract: The structural behaviour of steel-fibre-reinforced concrete beams was studied using non-linear finite-element analysis and existing experimental data. The work aim was to examine the potential of using steel fibres to reduce the amount of conventional transverse steel reinforcement without compromising ductility and strength requirements set out in design codes. To achieve this, the spacing between shear links was increased while steel fibres were added as a substitute. Parametric studies were subsequently car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…From the comparisons, it can be seen that the FE model presently employed was capable of providing accurate predictions for both modes of structural failure. As part of the current research project, further studies were carried out on the shear responses of SFRC simply-supported as discussed elsewhere [17]. Considering the findings in the preceding two sections, it can also be concluded that the FE model was successful in predicting the behaviour at both material and structural levels.…”
Section: Simply-supported Sfrc Beams With Conventional Reinforcement mentioning
confidence: 83%
See 1 more Smart Citation
“…From the comparisons, it can be seen that the FE model presently employed was capable of providing accurate predictions for both modes of structural failure. As part of the current research project, further studies were carried out on the shear responses of SFRC simply-supported as discussed elsewhere [17]. Considering the findings in the preceding two sections, it can also be concluded that the FE model was successful in predicting the behaviour at both material and structural levels.…”
Section: Simply-supported Sfrc Beams With Conventional Reinforcement mentioning
confidence: 83%
“…The structural configurations considered herein include a wide range of SFRC specimens ranging from simply-supported SFRC beams with no conventional reinforcement to more complex (statically indeterminate, consisting of more than one structural elements and subjected to a combination of axial and lateral loading) SFRC structural configurations fully reinforced. It should be pointed out that although some of the case studies are presented herein for the first time, others have formed the basis for parametric investigations carried out recently assessing the effect of the fibre-content on RC structural responses [14][15][16][17][18][19][20]. The reason for presenting all the cases in the present article is to show the objectivity of the numerical model employed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the calibration work was crucial in order to ascertain the accuracy of the numerical predictions. The generality of the NLFEA model adopted was validated on different SFRC structural configuration such as simply-supported beams (Abbas et al 2014b al. 2014c), in addition to the present continuous column case.…”
Section: Results Of Calibration Workmentioning
confidence: 99%
“…Continuing the theme of enhancing reinforced concrete element performance, Abbas et al (2014) outline a numerical modelling study used to examine the enhanced behaviour of reinforced concrete beams in shear. First, the available concrete constitutive modelling techniques for concrete were introduced.…”
mentioning
confidence: 99%